If it's not what You are looking for type in the equation solver your own equation and let us solve it.
36-7m=-7(m-5)
We move all terms to the left:
36-7m-(-7(m-5))=0
We calculate terms in parentheses: -(-7(m-5)), so:We get rid of parentheses
-7(m-5)
We multiply parentheses
-7m+35
Back to the equation:
-(-7m+35)
-7m+7m-35+36=0
We add all the numbers together, and all the variables
1!=0
There is no solution for this equation
| u+28=96 | | -2k-7k-(-10k)+4k=(-10) | | V=4/3x50.24 | | p=-6p+4 | | 48=8(x-1 | | z+12 = 33 | | 19=2/5x+3 | | –5+3b=3b-5 | | 90=1+12x+13x-6 | | 12e=16 | | 5+y-3=17 | | 16y-76=-44 | | 5÷x=2 | | 180=23x+1+27x-19 | | 81 +c=54 | | 14+9+x=180 | | 7=2y-8 | | x-21=-6 | | (6x6/9)-9Y=8(Y-4+9) | | 12g-8g-9g=20 | | 2(4u-5)=10 | | 2m+5=2m | | 3x+2=192 | | 11b-(-3b)-17b-(-19b)-b=(-15) | | (6x6/9)x2-9Y=8(Y-4+9 | | 3y+56=65 | | 36=9/16x×x | | 9x+10=-30 | | 8x=x-11 | | 2/4=x2 | | 2/3p+1=-p-5 | | w/2-12=7 |